125 A Case of Mistaken Identity: An Obsolete Anti-Reflux Device in An Older Patient with Variable Gastrointestinal Symptoms. (16th March 2021) - Squires, C; Porter, R; Ward, B
Abstract: Background: A frail 93-year-old lady presented with delirium and hypoxia, on a background of heart failure, constipation, cerebrovascular disease, and osteoporosis. A CTPA on admission revealed an unusual appearance of the left hypochondrium, leading to subsequent CT abdomen. This unexpectedly reported the presence of a gastric band. We therefore considered a possible misidentification as this procedure seemed unlikely in someone of her age. Her GP records revealed that she underwent surgical insertion of an Angelchik prosthesis in 1984. It transpired that our patient had experienced several longstanding symptoms, including reflux, bloating and constipation, which have all been observed in patients with Angelchik prostheses in situ. Discussion: The Angelchik prosthesis is an anti-reflux device for patients with chronic reflux disease with or without hiatus hernia, introduced in 1979. It comprised of an elastomer shell ring filled with silicone gel, that was sited at the lower oesophagus and secured with DACRON tapes. It was initially lauded for its replicable insertion technique and promising early results with around 30, 000 being inserted in mainly British and American Hospitals. However, over time it became apparent that a significant proportion of patients reported ongoing gastrointestinal symptoms due to device failure. Serious complications such as gastric perforations were also recognised. Surgical removal was noted to be technically complex, providing further challenges. The Angelchik prosthesis therefore fell from favour after a period of use of only fifteen years, and is now rarely encountered. We discovered that our patient had experienced multiple long-standing gastrointestinal complaints potentially linked to her prosthesis, though this association had not previously been considered. Whilst her frailty meant that removal would not be pragmatic, it is uncertain if this could have been a possible consideration in the past. This device is relevant to geriatricians as many recipients are now elderly, and may report ongoing symptoms.